Compliance costs of VAT for SMES in Algeria - Mansor, Muzainah; Tayib, Mahamad; Ferdjani, Mohamed Abdessadek (2016)
This study focuses on the tax compliance cost of VAT for SMEs in Algeria. The objective is to examine the internal compliance costs of VAT.This study used questionnaire survey to collect data from the respondents.Results obtained reveal that on average, Algerian SMEs spend 24,244 hours/month on the work related to VAT matters. Based on these total hours, a value of DZD 2,967,313 are spent on staffs’ salaries specifically for VAT-related work. This study also found that SMEs use low cost software to control their overall compliance cost. The result also shows that managers spend less time as compared to accountants for VAT compliance purposes but spend as much time as account staff for such matters.This study suggests that Algerian government needs to review the tax policy and tax administration with a view to reduce the tax compliance costs for VAT specifically for the case of SMEs in Algeria.